Acoustical design and experimental verification of school music rooms: A case study. (June 2016) - Ruggiero, Alessandro; Russo, Domenico
Abstract: This paper presents an approach to acoustical design and the results of a survey in music rooms in an Italian public school (Liceo Statale "Alfano I" in Salerno, Italy). The locations selected are devoted to orchestral performances and to recording. The purpose of correcting or insulating the spaces was to obtain a good acoustics in locations used at a reasonable cost. The acoustic correction was achieved by using sound-absorbing panels made from low-density polyethylene foam with a closed calibrated cell structure, placed on the walls and on the ceiling, and sound-insulation panels made of geometrically spherical composites. The optimal distribution of the sound absorbing panels was made using commercial software for simulating a scattering of sound pressure levels in a room. Reverberation time was measured at various frequencies with a class A phonometer, using an Integrated Impulse Response, in accordance with the international standard ISO 3382. For each measurement position variations of reverberation time in terms of time and frequency are measured. The results show a substantial accordance with the simulation in the design phase, allowing the authors to conclude that the proposed development is characterized by good performance in terms of cost-benefit.